Leaf Extract of Avicennia marina as an Antibacterial and Natural Preservative of Fresh Euthynus Affinis - Iswadi Iswadi; Samingan Samingan; Ida Sartika (Universitas Syiah Kuala, 2015)
The aim of this research was to determine the effectiveness of the leaf extract of the Avicennia marina as an antibacterial and natural preservatives to prolong the shelf life of the fish. The method used is the experimental method completely randomized design (CRD) non factorial, consisting of treatment concentration of 5%, 10%, 15%, 20% extract, positive control, and negative control. A number of bacterial colonies were analyzed by Anava and Duncan test (JNTD) at the level of 0.05. The results showed that the decline in the number of bacterial colonies on the treatment of 20% extract (P4) during the storage period of 12 hours and 24 hours of 34 and 37 colonies. Physical testing best fish in the extract 20% during the storage period of 12 hours of the appearance of clear eyes, skin taut, red gills, meat chewy and dense consistency. Organoleptic testing showed 20% extract treatment is much preferred by the panelists for aroma, flavor, color and texture of the fish is still very fresh. Based on the results of the study concluded that the use of Avicennia marina leaf extract is effective as an antibacterial and a natural preservative on the Euthynus affinis at a concentration of 20%